Padrões alimentares processados e ultraprocessados e a relação com a metilação dos genes BDNF e NR3C1 e o estado nutricional - Vieira, Tamires dos Santos (2023)
The change in the lifestyle of the population with the acquisition of unhealthy habits, such as the industrialized diet, have contributed to the growth of obesity, increase in the prevalence of diabetes, hypertension and other non-transmissible chronic diseases such as depression and cancer. Diet composition can act directly as a transcription factor, in addition to influencing epigenetic modifications, altering gene expression and contributing to the risk of diseases which can be transferred to offspring. Thus, the aim of this study was to evaluate the nutritional status and the relationship between adherence to processed and ultra-processed dietary patterns and levels of methylation of the BDNF and NR3C1 genes. This cross-sectional study collected data from 250 individuals between 20 and 59 years of age, using as indicators the Body Mass Index (BMI), HDL-C and LDL-C for dyslipidemia, TyG index for insulin resistance and symptoms suggestive of depression by the Beck Depression Inventory. The independent variables were socioeconomic factors (gender, age, education, location and income), psychosocial factors (stress, anxiety, depression and food insecurity), nutritional status (TyG Index, HDL-c, LDL-c, BMI, cortisol) and lifestyle (physical activity, smoking and alcoholism) used to adjust the generalized linear model (GLzM). The BDNF and NR3C1 genes methylation profile was evaluated by the pyrosequencing method. Dietary patterns were defined by factor analysis that assessed the interrelationship between commonly consumed foods, resulting in three patterns: healthy, industrialized and mixed. For the methylation of the BDNF sitespecific CpGs, it was decided to work separately, while for the NR3C1 CpGs, the main components were extracted, obtaining two components of CpGs. Comparisons of medians, Spearman correlations and linear models were used to assess the association between BDNF methylation and the 1F region of the NR3C1 gene. The prevalence of overweight and obesity was 33.5% and 39.9%, respectively. Furthermore, 64.9% of the individuals had insulin resistance, and more than 70.0% had an increased risk for metabolic complications related to abdominal adiposity, waistto-height ratio and conicity index. The present study showed that adherence to an unhealthy eating pattern and excess weight played a significant role in BDNF gene methylation, increasing the percentage of methylation (p<0.05). In addition, the lower methylation in the total segment and in component 1 (CpG 44-47) of NR3C1 can be explained by overweight and adherence to the industrialized pattern, when controlled for covariates. And this evidence helps to understand the epigenetic role of adherence.